The book of hiding: gender, ethnicity, annihilation, and Esther - Beal, Timothy K. (Biblical limits, 1997)
The Book of Hiding offers a fluent and erudite analysis of the parallels between the Bible and contemporary discussions of gender, ethnicity and social ambiguity